A Site of Bounded Imaginaries: Local Narratives of Buan after Protests against a Nuclear Waste Repository. Issue 3 (3rd July 2021) - Chung, Seungmi; Kim, Kun Hee; Park, Yeseul; Kim, Hyomin
Abstract: This paper examines a historical case where local residents in South Korea had been alienated from the decision-making processes in nuclear policy as their sociotechnical visions remained marginalized. Narratives of nuclear experts, activists in environmental NGOs (ENGOs), and local residents supporting or resisting against the siting of a repository in a southwestern rural town, Buan, from 2003 to 2005 were used for our comparative textual analyses. Imaginaries of desirable forms of life and order that constitute nationally-shared visions of "good society" profoundly delimit the shapes of futures by enabling key political decisions of a nation. With our findings, we argue that ethical problems of how to recognize and compensate for what has already happened to people around (candidate) sites of nuclear facilities remains a source of latent social conflict. Buan residents' visions of a "good society" attainable through their practices around nuclear technology were collectively held and publicly narrated yet failed to become widely shared in the nation. If local people's understanding of what the past has been and what the future should be like continue to stay marginalized, Korean nuclear governance with participatory initiatives will remain in its current form of "partial" inclusiveness.